TEST YOUR MEMORY (TYM) TESTING IN NON-ALZHEIMER DEMENTIAS. (29th November 2012) - Brown, J; Reddy, S; Cunningham, K; Dong, H; Ibram, F; Clatworthy, P; Wiggins, J
Abstract : The Test Your Memory (TYM) test is a short cognitive test. It is completed by the patient and supervised by a clinic nurse and so takes minimal medical time. It is a useful screening test for Alzheimer's disease (AD)1. This study examines the use of the TYM in non-Alzheimer dementias. Over 100 patients with Frontotemporal dementia (FTD) and Dementia with Lewy bodies (DLB) were recruited. All completed the TYM test, most completed the Addenbrooke's Cognitive Examination (ACE-R) and the mini-mental state examination (MMSE). Patients with non-AD dementia scored an average of (33/50) on the TYM test, this was significantly worse than age matched controls (46/50). The patients scored an average of 24/30 on the MMSE (above the dementia cut off) and 66/100 on the ACE-R. The TYM score correlated strongly with the ACE-R score (Pearson corr. coeff.=0.84). Average TYM scores were significantly different from controls in all forms of FTD (behavioural variant=34, semantic dementia= 26, progressive aphasia= 4) and in DLB (35).The pattern of TYM scores varied between the various forms of FTD and between FTD and AD. There were less marked differences between patients with DLB and AD.